SEARCHING CERTAINTY FACTOR METHOD IN DIAGNOSIS OF SKIN DISEASES IN CHILDREN - Vivi Amalianti Nasution VIvi Amalianti Nasution; Rizaldi; Wiwin Handoko (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Skin diseases in Indonesia are generally caused by bacterial, fungal, viral infections, and due to allergies, in contrast to Western countries which are heavily influenced by degenerative factors. Another factor of skin disease is people's habits and an unclean environment. The purpose of this research is to build an expert system for diagnosing skin diseases in children based on web. Calculation of uncertainty in an expert system can be done by several methods of uncertainty. One of them is to use the Certainty Factor method. The result of the implementation of the system is that the system provides choices in the form of symptoms that must be answered by the patient based on the symptoms experienced by the patient and the results of the process the system will provide information about what type of skin disease in children is experiencing in order to get a solution. Keywords: Expert System, Diagnosis, Skin Diseases in Children, Certainty Factor, Web